Isorhamnetin glycoside isolated from Opuntia ficus-indica (L.) MilI induces apoptosis in human colon cancer cells through mitochondrial damage. (1st September 2019) - Antunes-Ricardo, Marilena; Hernández-Reyes, Annia; Uscanga-Palomeque, Ashanti C.; Rodríguez-Padilla, Cristina; Martínez-Torres, Ana Carolina; Gutiérrez-Uribe, Janet Alejandra
Abstract: This work aimed to evaluate the mechanisms involved in the apoptosis induction of isorhamnetin-3- O -glucosyl-pentoside (IGP) in metastatic human colon cancer cells (HT-29). To achieve this, we assessed phosphatidylserine (PS) exposure, cell membrane disruption, chromatin condensation, cell cycle alterations, mitochondrial damage, ROS production, and caspase-dependence on cell death. Our results showed that IGP induced cell death on HT-29 cells through PS exposure (48%) and membrane permeabilization (30%) as well as nuclear condensation (54%) compared with control cells. Moreover, IGP treatment induced cell cycle arrest in G2/M phase. Bax/Bcl-2 ratio increased and the loss of mitochondrial membrane potential (63%) was observed in IGP-treated cells. Finally, as apoptosis is a caspase-dependent cell death mechanism, we used a pancaspase-inhibitor (Q-VD-OPh) to demonstrate that the cell death induced by IGP was caspase-dependent. Overall these results indicated that IGP induced apoptosis through caspase-dependent mitochondrial damage in HT-29 colon cancer cells. Highlights: Isorhamnetin glycoside IGP treatment induces cell cycle arrest in G2/M phase. Isorhamnetin glycoside IGP induced apoptosis by the modulation of the Bax/Bcl-2 expression. IGP induced apoptosis through mitochondrial damage and the increase of ROS levels.